The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13045-021-01064-8
|View full text |Cite
|
Sign up to set email alerts
|

Myeloproliferative neoplasm-driving Calr frameshift promotes the development of pulmonary hypertension in mice

Abstract: Frameshifts in the Calreticulin (CALR) exon 9 provide a recurrent driver mutation of essential thrombocythemia (ET) and primary myelofibrosis among myeloproliferative neoplasms (MPNs). Here, we generated knock-in mice with murine Calr exon 9 mimicking the human CALR mutations, using the CRISPR-Cas9 method. Knock-in mice with del10 [Calrdel10/WT (wild−type) mice] exhibited an ET phenotype with increases of peripheral blood (PB) platelets and leukocytes, and accumulation of megakaryocytes in bone marrow (BM), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Mouse hematopoietic cells were prepared, as described previously [ 12 , 13 ]. Briefly, peripheral blood cells of mice were drawn from the tail vein and counted by XT-1800i (Sysmex, Kobe, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse hematopoietic cells were prepared, as described previously [ 12 , 13 ]. Briefly, peripheral blood cells of mice were drawn from the tail vein and counted by XT-1800i (Sysmex, Kobe, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Functional analysis of the CALR mutant, which is the second most frequent driver mutation in MPNs, has been insufficient, especially regarding its collaboration with other mutations. Recently, we generated Calr -del10 mice that lack 10 base pairs in exon 9 of Calr , mimicking type2-like CALR mutation in MPN patients; these mice presented mild phenotypes of MPN 98) . Our preliminary data have shown that addition of Hmga2 -Tg to Calr -del10 evokes progression of MPN phenotypes but not myelofibrosis or leukemic transformation, while deletion of Ezh2 can provoke myelofibrosis or leukemic transformation after a long latency.…”
Section: The Role Of Hmga2 In Myeloid Malignanciesmentioning
confidence: 99%
“…Specific pathological features, such as fibrosis alterations, can be detected via histopathological assessment at the early stage of PH progression [ 3 ]. Both external and internal stimuli, such as genetic mutations, hypoxia, cold exposure, air pollution, and respiratory infection, can initiate immune responses and therefore lead to the proliferation of vascular cells, autoantibody formation, and dysregulated immunity [ 16 – 20 ]. Histopathological evidence has suggested that perivascular infiltration of inflammatory cells is common in PH and precedes structural remodelling in vessels [ 5 , 6 , 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%